EVIDENCES FOR STRONG MIXED-POLARITY MAGNETIC FIELDS IN AREA OF A SEISMIC SOURCE ASSOCIATED WITH LARGE PROTON SOLAR FLARE - Lozitsky, V. G.; Baranovsky, E. A.; Lozitska, N. I.; Tarashchuk, V. P. (Одеські астрономічні публікації, 2019)
We present in a concise statement the new results based on spectral-polarization measurements of magnetic fields in an extremely powerful proton solar flare on October 28, 2003 of X17.2 / 4B class. The observation material was obtained with Echelle spectrograph of HST AO KNU, which makes it possible to analyze the spectral manifestations of the Zeeman effect in very many lines of the visible region of the spectrum, including the photospheric and chromospheric lines. The I ± V and V profiles of about ten FeI and FeII lines, as well as the Hα, Hβ, Hγ, and Hδ lines were studied in a area of the seismic source of the flare, which was localized in the sunspot penumbra of S magnetic polarity. In this flare, we found an unprecedented Balmer decrement of intensities of Hα and Hβ lines which corresponds to ratio I (Hβ) / I (Hα) = 1.68. In the FeI 5434.5 line with very low Lande factor (g eff = –0.014), a reliable splitting of emission peaks was found, which could indicate superstrong magnetic fields (about 50 kG) of N polarity. Indications for magnetic fields with intensity ≈ 12 kG of S polarity were found too. These indications are based on the study of the Stokes V profile of FeII 5234.6 line. In this line, there were two positive and two negative peaks of profile V, indicating a two- component structure of the magnetic field. According to the simulation data, the small-scale component with the above-mentioned superstrong magnetic field had a filling factor about 0.1 and had narrow (about twice) the half- widths of the line profiles. The close contact of subtelescopic magnetic fields of different magnetic polarity, but of lower intensity (B ≈ 1 kG) was also indicated by the comparison of the half-widths of the FeI 5247.1 and 5250.2 lines. In general, it can be concluded that the necessary conditions for the reconnection of magnetic lines were fulfilled even at the photospheric level, rather than in the corona or chromosphere, as suggested by theoretical models of solar flares.